Spraying Methods, Personal Hygiene, and Use of Personal Protective Equipment are Related to Pesticide Poisoning at Farmers - Amin, Nur Rachmatullah; Ibrahim, Hasbi; Nildawati, Nildawati; Habibi, Habibi (Public Health Science & Religion, 2024)
Background: The World Health Organization (WHO), estimates 1-5 million cases of pesticide poisoning in agricultural workers with a mortality rate of 220,000 fatalities. This study aims to determine the determinants of poisoning in vegetable farmers who use pesticides in Kanreapia Village, Tombolopao District, Gowa Regency. Methods: This study uses a type of cross-sectional study, by taking a population of 88 vegetable farmers. Sampling was carried out using purposive sampling with a sample of 44 respondents. Results: The results of the study found that factors related to the determinants of poisoning in vegetable farmers using pesticides were the method of spraying, personal hygiene, and the use of PPE. Meanwhile, the length of work and the period of service have no relationship with the incident. Conclusion: This study recommends that farmers pay attention to the use of PPE such as masks and gloves when mixing pesticides, as well as pay attention to personal hygiene after spraying.